Proportional Trends in Pediatric Opioid Prescribing Between 2005 and 2016 by Age Group, Sex, Ethnicity, Race, Language, and Payer Status from a Large Children’s Hospital in the Southwest United States - Melissa Pielech; Eric Kruger; Samantha M. Portis; Khirsten J. Wilson; W. Evan Rivers; Kevin E. Vowles (Children)
Background/Objectives: Prescription opioid use before adulthood is typically effective for acute pain control and is also associated with adverse short- and long-term consequences. Methods: This study examined pediatric opioid prescribing trends over time across different age groups (early childhood, school age, adolescence, young adult) and sociodemographic subgroups (sex, ethnicity, race, language, payer type) from 2005 to 2016. Results: Utilizing 42,020 first outpatient opioid prescriptions for youth aged 0–21 years from a large US children’s hospital, this research found notable trends and disparities. Prescription rates increased by 35% from 2005–2007 to 2008–2010, then decreased by 14% from 2008–2010 to 2011–2013, and decreased again by 22% from 2011–2013 to 2014–2016. Chi-squared tests indicated significant changes in prescription rates across all sociodemographic subgroups, though only age group, ethnicity, and payer type (i.e., the party responsible for payment for hospital services) had changes with non-negligible effect sizes (Cramer’s V). Specifically, age group showed small to medium effects (V = 0.16), while ethnicity and payer demonstrated small effects (V = 0.10 each). This study highlights variations in opioid prescribing trends, particularly among different age groups, ethnicities, and payer statuses up to 2016. Conclusions: These findings reveal differing trends in pediatric opioid prescribing during the peak of the opioid epidemic, highlighting the importance of considering age and sociodemographic variables for understanding prescribing patterns fully and raising potential concerns about inequities in pain management. Future studies should explore similar trends from 2016 onward.